Trust and Foreign Direct Investment: An Empirical Analysis - Bohdan Kukharskyy (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
This paper studies the relationship between trust and foreign direct investment (FDI) in a crosssection of countries. Accounting for the issue endogeneity, this paper suggests that countries with a higher level of generalized trust attract more FDI than the low-trust countries.
Keywords: F14; F21; 330; Trust; Foreign Direct Investment; Causality